Integration of Submerged Aquatic Vegetation Motion Within Hydrodynamic Models. Issue 8 (21st August 2020) - Nakayama, K.; Shintani, T.; Komai, K.; Nakagawa, Y.; Tsai, J. W.; Sasaki, D.; Tada, K.; Moki, H.; Kuwae, T.; Watanabe, K.; Hipsey, M. R.
Abstract: Aquatic models used for both freshwater and marine systems frequently need to account for submerged aquatic vegetation (SAV) due to its influence on flow and water quality. Despite its importance, parameterizations are generally adopted that simplify feedbacks from SAV, such as canopy properties (e.g., considering the deflected vegetation height) and the bulk friction coefficient. This study reports the development of a fine‐scale non‐hydrostatic model that demonstrates the two‐way effects of SAV motion interaction with the flow. An object‐oriented approach is applied to capture the multiphase phenomena, whereby a leaf‐scale SAV model based on a discrete element method is combined with a flow dynamics model to resolve stresses from currents and waves. The model is verified through application to a laboratory‐scale seagrass bed. A force balance analysis revealed that leaf elasticity and buoyancy are the most significant components influencing the horizontal and vertical momentum equations, respectively. The sensitivity of canopy‐scale bulk friction coefficients to water depth, current speeds, and vegetation density of seagrass was explored. Deeper water was also shown to lead to a smaller decrease in vegetation height. The model approach can contribute to improving assessment of processes influencing water quality, sediment stabilization, carbon sequestration, and SAV restoration, thereby supporting an understanding of how waterways and coasts will respond to changes brought about by development and a changing climate. Plain Language Summary: Aquatic system models that capture aquatic vegetation are increasingly important to help us understand processes controlling carbon budgets (e.g., "blue carbon") and for planning restoration efforts (e.g., Adams et al., 2016, https://doi.org/10.1002/lno.10319 ). Current models all rely on "static" approaches to account for vegetation via bulk parameterizations, though we know vegetation motion is important (e.g., Abdolahpour et al., 2018, https://doi.org/10.1002/lno.11008 ). Our study is the first to model the feedback between blade‐scale vegetation motion and hydrodynamics to show it is crucial in shaping bottom mixing processes with implications for carbon and nutrient deposition. Key Points: A model is presented to capture the changing position of Submerged Aquatic Vegetation blades and validated using laboratory experiments Forcing terms that control seagrass movement within a meadow are evaluated Estimates of deflected vegetation height and bulk meadow friction coefficients demonstrate the importance of simulating SAV motion